(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
Public speaking is an art. It requires one to cover several important aspects. A good speaker must know the right words to use in order tokeep the audience captivated. The selection of the right words is not only animportant aspect in understanding the subject matter, but it also helpsthe audience remember the speech for days to come.